OTDR technology - Shum, Ping (2012)
Optical fiber-based technologies, such as optical fiber communication networks and fiber-optic sensors are becoming more and more commonly used. How to ensure rapid, stable and reliable transmission of information in an optical fiber link is becoming more and more critical. To achieve this goal, we must ensure the reliability of the optical fiber communication or sensing system. We should develop a practical technique to monitor the system effectively to guarantee its timely and accurate maintenance.